HAEMATOLOGICAL ALTERATIONS FOLLOWING VARIOUS THERAPIES IN SURT.I BUFFALOES WITH POSTPARTUM METRITIS - PATIL, R D; PATEL, J A; HADIYA, K K; DHAMl, A J (The Indian Journal of Animal Reproduction, 2023)
This study was carried out under field condition on 40 Surti buffaloes with postpartum metritis divided intofive groups of eight animals each. The study included use of four treatment lines and one control group, viz.,Group 1- Metronidazole (500 mg) 1/U for 5 days; Group II- Ciprofloxacin (1500 mg) and Tinidazole (1800 mg)1/U for 5 days; Group Ill- Ciprofloxacin (1500 mg) and Tinidazole (1800 mg) 1/U for 5 days plus PGF2, 25 mg i/monce on first day; Group IV- Ceftlofur (long acting)@ 6.6 mg/kg body weight subcutaneously once and Group V(control)- Normal saline 1/U for 5 days. The effects of these therapeutic regimes were evaluated by comparingthe clinical and haematological alterations before and 6 days after treatment. The mean values of Hb, PCVand TEC after four treatments were significantly (P
Keywords: Buffalo; Postpartum metritis; Therapy; Haematological alterations